2022
DOI: 10.1038/s41433-022-01966-y
|View full text |Cite
|
Sign up to set email alerts
|

Teaching home tonometry using a remote video link

Abstract: Background/Objectives Intraocular pressure (IOP) is the primary modifiable risk factor in the progression of glaucoma. The ICare HOME is a self-tonometer which empowers patients to measure their own IOP and allows a more complete picture of diurnal IOP. This project aims to determine the feasibility of teaching patients to perform self-tonometry remotely using a remote video link. Subjects/Methods This prospective study involved 12 patients with glaucoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Given the potential for the iCare HOME tonometer to provide more complete IOP profiling, Barbour-Hastie and Tatham explored whether at-home tonometry could realistically be taught to patients with glaucoma. The prospective study of 12 patients with an average age of 60 years found that only 2 were unable to record diurnal measurements at home after remote teaching [18 ▪▪ ].…”
Section: Tonometrymentioning
confidence: 99%
“…Given the potential for the iCare HOME tonometer to provide more complete IOP profiling, Barbour-Hastie and Tatham explored whether at-home tonometry could realistically be taught to patients with glaucoma. The prospective study of 12 patients with an average age of 60 years found that only 2 were unable to record diurnal measurements at home after remote teaching [18 ▪▪ ].…”
Section: Tonometrymentioning
confidence: 99%